The Curriculum Design for Scholarly Communication - Yuan-Ho Huang; Tzu-Heng Chiu; Hsin-Liang Chen (Tūzī yǔ dàng’àn xuékān)
The provision of scholarly communication services by university libraries in Europe and the United States has gradually become widespread. However, formal educational training programs related to scholarly communication competencies seem to be insufficient. This study explores the current scholarly communicationrelated courses in North America and Taiwan and examines the scholarly communication courses from 8 universities listed on the websites of American Library Association (ALA)-accredited Master’s programs in Library and Information Science. Additionally, focus group interviews were conducted to gather insights from educators in Taiwan. The findings propose a curriculum outline for scholarly communication encompassing the following seven dimensions: the development background and influencing factors of scholarly communication, academic publishing and peer review, open science and open access issues, intellectual property rights and copyright, technical issues in digital publishing and archiving, metrics for evaluating scholarly outputs and impact, and the role of librarians along with future trends. Each dimension includes two to six subtopics. This curriculum outline can serve as a reference for the development of the scholarly communication curriculum in Taiwan and for future librarian training to enhance the quality of scholarly communication services.